A focused netnographic study exploring experiences associated with counterfeit and contaminated anabolic-androgenic steroids - Evelyn Frude; Fiona H. McKay; Matthew Dunn (BMC, 2020)
Abstract Background A primary consequence of illicit drug markets and the absence of regulation is the variable quality or purity of the final product. Analysis of anabolic-androgenic steroid seizures shows that these products can contain adulterated products, product not included on the label, or product of unsatisfactory standard. While the potential negative effects of counterfeit anabolic-androgenic steroids (AAS) use is a recognised risk associated with use, no study has explored personal experiences associated with use. The aim of the present study was to use online discussion forums to investigate and explore the experiences associated with the purchase and consumption of counterfeit AAS among consumers. Methods An online search was conducted to identify online forums that discussed counterfeit or contaminated AAS; three were deemed suitable for the study. The primary source of data for this study was the 'threads' from these online forums, identified using search terms including 'counterfeit', 'tampered', and 'fake'. Threads were thematically analysed for overall content, leading to the identification of themes. Results Data from 134 threads (2743 posts from 875 unique avatars) was included. Two main themes were identified from the analysis: (1) experiences with counterfeit product and (2) harms and benefits associated with counterfeit product. Conclusions The use of counterfeit or contaminated substances represents a public health concern. Those who report using performance and image enhancing drugs such as AAS for non-medical purposes report consuming these substances and experiencing harm as a result. Consumers take steps to limit coming into contact with counterfeit or contaminated product, though recognise that many of these have limitations. The implementation of accessible drug safety checking services may provide an opportunity to provide consumers with information to assist them with making healthier choices.